The MAIN RISK FACTORS OF AMERICAN FOULBROOD SPREADING IN HONEY BEES IN SERBIA - Vladimir Polaček; Biljana Đurđević; Jasna Prodanov-Radulović; Jelena Petrović; Radomir Ratajac; Sandra Jakšić; Milica Živkov-Baloš (Archives of Veterinary Medicine, 2021)
American foulbrood (AFB) is one of the most important contagious honey bee diseases. In Serbia, it is mandatory to report AFB, and this disease is registered in our country every year. Starting from 2018, active surveillance of the presence of the AFB has been conducted throughout the country. The paper analyzes the data on the occurrence of AFB during the period between 2019 and 2021 from official disease reports in the National Animal Disease Notification System "VetUp". The results of this research indicate that AFB appears every year in the Republic of Serbia, despite the measures that are being applied. The results indicate that in 36 settlements in the country, this disease has reoccurred in the same localities in the observed period. Namely, in 17 localities AFB occurred consecutively in the 2019-2020 period , while in 21 localities the disease was re-registered consecutively in the period between 2020 and 2021 (until 6.11.2021), and it reoccurred in 2021 in 9 localities, compared to the registered cases of AFB in 2019. It was found that the disease has consecutively been reoccurring in 5 location between 2019 and 2021 in the same locations. The fact that the disease has been occurring for several years in the same places speaks in favor of the fact that the control measures applied in the control of this disease are not effective enough. Continuing education of beekeepers, veterinarians and veterinary inspection in the field of diagnosis and effective decontamination and neutralization of all potencional sources of AFB reinfections, revision of current legislation, as well as raising awareness of the importance of early diagnosis of as many cases of this disease as possible are the key factors in successful AFB control.